RETROSPECTIVITY AND HUMAN RIGHTS IN INDONESIA: HOW CAN IRREGULARITIES BE RESOLVED - Suhaeb, Irsyad Dhahri S (UI Scholars Hub, 2013)
To join the international community in committing protection to human rights, Indonesia consequently manifested the commitment through its constitution. However, there are still homework need to be done, including how to clarify the meaning of retrospective, also acknowledged as ‘retroaktif’, indicated in the Article 28I (1) of the 1945 Constitution. Three retrospective cases decided by the Constitutional Court were used to examine Indonesian practitioners’ understanding on retrospective principle in line with human rights, they are cases of Masykur of Terrorism Law, Abilio Soares of Human Rights Court Law, and ex members of banned political Party-PKI in General Election Law. Through these cases, it is interestingly seen that retrospective issues of human rights were implemented variously according to the interests in national socio-political needs. This made retrospectivity issue within human rights still open to be discussed more in setting up Indonesian human rights.